Catecholaminergic polymorphic ventricular tachycardia managed as orthostatic dysregulation and epilepsy in 11‐ and 15‐year‐old sisters. Issue 11 (22nd November 2018) - Fujita, Shuhei; Nishida, Keigo; Irabu, Hitoshi; Nakagawa, Ryo; Futatani, Takeshi; Igarashi, Noboru; Usuda, Kazuo; Nagata, Yoshiki; Ohno, Seiko; Horie, Minoru; Hatasaki, Kiyoshi
Abstract: Background: In pediatric patients, syncope commonly occurs as vasovagal syncope, or in epilepsy or orthostatic dysregulation. Cardiogenic syncope is rare but it is lethal, and needs to be promptly diagnosed and treated. Methods and Results: We describe the cases of 11‐ and 15‐year‐old sisters with frequent syncope during exercise and emotional stress since the age of 10 and 12, respectively. There were no abnormalities on 12‐lead electrocardiogram (ECG) at rest. They were first diagnosed with orthostatic dysregulation and epilepsy. Because of recurrent exercise‐induced syncope, cardiac examinations were performed. On treadmill exercise stress test, bidirectional ventricular tachycardia was induced in the 11‐year‐old girl, which degenerated into ventricular fibrillation; frequent polymorphic premature ventricular contractions were induced in her elder sister. They were diagnosed with catecholaminergic polymorphic ventricular tachycardia (CPVT) and started on oral beta‐blockers and exercise restriction. Conclusions: It is important to suspect CPVT in pediatric exercise‐induced syncope, and to recognize that CPVT does not show ECG abnormalities at rest.